(untitled) (Journal for Studies in Humanities and Social Sciences, 2014)
The Millennium Development Goals (MDGs) and the eradication of poverty ore two concerns that are highly supported by African governments, bilateral agencies and the United Nations. However within Africa, not much research has been done on what role libraries and information services can play towards meeting the goals of the MDG programme and the eradication of poverty. The aim of this paper is to present preliminary findings from a study in Greenwell Matongo, Katutura, Windhoek, on information needs for poverty eradication in the context of MDGs. Focus group discussions were conducted with three groups consisting of young females, young males, and adults respectively. The participants described the high levels of poverty in their community, and the low levels of hygiene and sanitation. There was recognition that education for children is important to overcome poverty. Gender relations are marked by alcohol related violence and rapes. The rate of HIV/A!DS and TB infection were thought to be high but kept secret because of fear of stigma. There were serious environmental problems in the community because of the use of inflammable fuel sources such as p araffin and candles in the corrugated iron shacks. The community information centre in the settlement is used intensively by young people for educational purposes, but only marginally, by adults for photocopying and literacy purposes. Recommendations are made on how to address the identified information needs of the community and capacity building in the context of MDG and poverty eradication.